Ewolucja paradygmatu procesu karnego - Skorupka, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The paradigm of criminal procedure comprises basic fundamental principles that express ideas which should be applied in the course of criminal proceedings, as well as the objective of the proceedings and the method way to achieve it. Over the course of history, the paradigm of criminal procedure has changed. Today, authors dealing with the subject agree that the main objective of criminal procedure is to enforce the material criminal law. In addition, criminal procedure is to establish the material truth. The structure and organisation of criminal procedure, the main objective of which is to implement the norms of the material criminal law, are based primarily on the principles of legalism and material truth, which ensure effective implementation of the material criminal law. Criminal procedure cannot, therefore, be equated solely with a set of measures and actions that make it possible to enforce the material criminal law. The aim of criminal procedure is not only to implement the norms of the material criminal law. Just as important, after all, is to organise criminal proceedings in a way that makes them fair and honest with regard to the parties or other participants. Only if these principles are observed, can proceedings be regarded as fair. The enforcement of the material criminal law as the objective of criminal procedure cannot justify the means in the form of dishonest or unfair proceedings. In such a situation, the application of the norms of the material criminal law cannot be regarded as done in a fair manner. Both objectives of criminal procedure, namely justice with regard to material criminal law and procedural justice, are thus complementary.
Keywords: postępowanie karne; rzetelność postępowania karnego; paradygmat